2004
DOI: 10.1161/01.cir.0000130647.29030.90
|View full text |Cite
|
Sign up to set email alerts
|

Role of Akt Signaling in Mitochondrial Survival Pathway Triggered by Hypoxic Preconditioning

Abstract: Background-The signaling pathways that control ischemia/reperfusion-induced cardiomyocyte apoptosis in heart have not been fully defined. In this study, we investigated whether Akt signaling has a role in the antiapoptotic pathways of preconditioning against hypoxia/reoxygenation (H/R). Methods and Results-Primary cultures of adult rat ventricular myocytes (ARVMs) were subjected to preconditioning (PC) by exposing the cells to 10 minutes of hypoxia followed by 30 minutes of reoxygenation. Non-PC and PC myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 43 publications
6
102
0
Order By: Relevance
“…Adaptation of the myocardium to ischemia involves alteration of several signaling pathways (i.e., ERK1͞2, AKT, protein kinase C, and͞or phospholipase C) involved in collateral growth (32,33), apoptosis (33,34), energy metabolism (33,35), and the development of a ''preconditioned'' myocardium. G␤␥ signaling is clearly involved in many aspects of such signaling pathways (36)(37)(38)(39). AGS8 provides an unexpected mechanism for regulation of the G protein activation cycle and is specifically induced in the heart in response to transient repetitive ischemia and͞or hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation of the myocardium to ischemia involves alteration of several signaling pathways (i.e., ERK1͞2, AKT, protein kinase C, and͞or phospholipase C) involved in collateral growth (32,33), apoptosis (33,34), energy metabolism (33,35), and the development of a ''preconditioned'' myocardium. G␤␥ signaling is clearly involved in many aspects of such signaling pathways (36)(37)(38)(39). AGS8 provides an unexpected mechanism for regulation of the G protein activation cycle and is specifically induced in the heart in response to transient repetitive ischemia and͞or hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…This ratio is a marker of increased cardiomyocyte survival probability (Condorelli et al 1999). Furthermore, apo A-I transfer normalised the diabetes-reduced phosphorylation of the pro-survival protein kinase B Akt (Montanari et al 2005;Uchiyama et al 2004) and of its effector eNOS to levels found in non-diabetic hearts ). This finding was further corroborated by experiments in cardiomyocytes.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-associated Cardmentioning
confidence: 92%
“…Another condition that could accentuate the susceptibility of the mitochondria to elevated Ca 2ϩ is the diminished Akt activity that we previously reported occurred as early as 8 h after virus removal and contributed to Q209L-induced apoptosis (15). Akt has been shown to contribute to preservation of mitochondrial integrity in ischemic preconditioning and in response to ischemia reperfusion (32)(33)(34). Thus, both the increased ROS and the decreased Akt that occur in the intact cell would likely render the mitochondria more susceptible to disruption.…”
Section: Camentioning
confidence: 91%